Chlorella: 125 years of the green survivalist. (February 2015) - Krienitz, Lothar; Huss, Volker A.R.; Bock, Christina
<x xml:space="preserve">Abstract</x> Chlorella, the archetype of unicellular green algae, is a high-performance primary producer in aquatic and terrestrial ecosystems. Under the simple spherical morphology of Chlorella, many other 'green balls' unfolded as independent phylogenetic lineages as a result of convergent evolution. By contrast, green algae with strikingly different phenotypes were unmasked as close relatives of Chlorella by modern molecular techniques. Here, we point to the increasing impact of these diverse protists on ecology, evolution, and biotechnology in the light of integrative taxonomy.